Anti-Angiogenetic and Anti-Lymphangiogenic Effects of a Novel 2-Aminobenzimidazole Derivative, MFB - Hsu, Ming-Jen; Chen, Han-Kun; Chen, Cheng-Yu; Lien, Jin-Cherng; Gao, Jing-Yan; Huang, Yu-Han; Hsu, Justin Bo-Kai; Lee, Gilbert Aaron; Huang, Shiu-Wen (Frontiers in Oncology, 2022)
Background and purpose: Benzimidazoles have attracted much attention over the last few decades due to their broad-spectrum pharmacological properties. Increasing evidence is showing the potential use of benzimidazoles as anti-angiogenic agents, although the mechanisms that impact angiogenesis remain to be fully defined. In this study, we aim to investigate the anti-angiogenic mechanisms of MFB, a novel 2-aminobenzimidazole derivative, to develop a novel angiogenesis inhibitor. Experimental approach: MTT, BrdU, migration and invasion assays, and immunoblotting were employed to examine MFB’s effects on vascular endothelial growth factor (VEGF)-induced endothelial cell proliferation, migration, invasion, as well as signaling molecules activation. The anti-angiogenic effects of MFB were analyzed by tube formation, aorta ring sprouting, and matrigel plug assays. We also used a mouse model of lung metastasis to determine the MFB’s anti-metastatic effects. Key results: MFB suppressed cell proliferation, migration, invasion, and endothelial tube formation of VEGF-A-stimulated human umbilical vascular endothelial cells (HUVECs) or VEGF-C-stimulated lymphatic endothelial cells (LECs). MFB suppressed VEGF-A and VEGF-C signaling in HUVECs or LECs. In addition, MFB reduced VEGF-A- or tumor cells-induced neovascularization in vivo. MFB also diminished B16F10 melanoma lung metastasis. The molecular docking results further showed that MFB may bind to VEGFR-2 rather than VEGF-A with high affinity. Conclusions and Implications: These observations indicated that MFB may target VEGF/VEGFR signaling to suppress angiogenesis and lymphangiogenesis. It also supports the role of MFB as a potential lead in developing novel agents for the treatment of angiogenesis- or lymphangiogenesis-associated diseases and cancer.